Peculiarities of structural-functional indicators of the heart in the combined of hypertension and gastroesophageal reflux disease in liquidators of consequences of Chornobyl accidents - Tkachenko , Nataliia; Sinelnik , Viktoria; Protsenko, Olena (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
The Chornobyl accident in Ukraine affected more than 3 million people. The impact of the disaster on human health is multifaceted and is associated with both the direct effects of ionizing radiation and other negative factors of the accident. Diseases of the circulatory system are one of the leading causes of death in this population. The combination of hypertension disease and gastroesophageal reflux disease reveals forms of structural and functional indicators of the heart, characterized by a higher level of left ventricular myocardial hypertrophy, regardless of the stage of HD and the degree of blood pressure. The aim was to determine the features of structural and functional indicators of the heart in the combined course of HD and GERD in the liquidators of the Chornobyl accident, as well as to establish differences from the indicators of patients with isolated HD. Materials and methods of research. A comprehensive survey of 105 liquidators of the Chornobyl accident aged 52 to 69 years (mean age 58.5 ± 0.8 years), 85.7 % of men and 14.3 % of women was conducted. All of them were hospitalized in therapeutic and / or observed on an outpatient basis in the outpatient departments of the «Regional Clinical Specialized Dispensary for Radiation Protection of the Population» of Kharkiv. Patients were divided into 2 groups. The first group – 52 patients with a combined course of HD and GERD, 44 (84.6 %) men and 8 (15.4 %) women. The second – 53 patients with isolated HD, 46 (86.8 %) men and 7 (13.2 %) women. All patients in outpatient settings underwent a comprehensive medical examination, including Doppler echocardiography. Results and conclusions. When comparing the structural and functional parameters of the heart in the combined course of HD and GERD in the liquidators of the Chornobyl accident with an isolated course of HD, it was found that almost all indicators of systolic, diastolic and pumping heart function are statistically significantly increased, p ≤ 0.05, except for aortic pressure size gradient and diameter of right ventricule. Thus, patients with a combined course of pathology have more pronounced changes in the structural and functional parameters of the heart, thereby increasing the risk of cardiovascular complications. Prospects for the study are relevant and necessary for further prediction of the risk of complications and individual therapeutic approach in comorbid pathology in the liquidators of the Chernobyl accident.